2013
DOI: 10.1183/09031936.00082413
|View full text |Cite
|
Sign up to set email alerts
|

Role of activin-A in cigarette smoke-induced inflammation and COPD

Abstract: Activin-A is a pleiotropic cytokine belonging to the transforming growth factor-b superfamily and has been implicated in asthma and pulmonary fibrosis. However, the role of activin-A and its endogenous inhibitor, follistatin, in the pathogenesis of chronic obstructive pulmonary disease (COPD) is unknown.We first quantified activin-A and follistatin in the lungs of air-or cigarette smoke-exposed mice and in the lungs of patients with COPD by immunohistochemistry, ELISA and quantitative real-time PCR. We subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 40 publications
2
36
0
Order By: Relevance
“…In conclusion, the study of VERHAMME et al [9] sheds light on the role of activin-A and follistatin in COPD, and motivates further investigation. Persistent and exaggerated production of activin-A might be a key factor provoking persistent inflammation in COPD.…”
Section: @Erspublicationsmentioning
confidence: 70%
See 2 more Smart Citations
“…In conclusion, the study of VERHAMME et al [9] sheds light on the role of activin-A and follistatin in COPD, and motivates further investigation. Persistent and exaggerated production of activin-A might be a key factor provoking persistent inflammation in COPD.…”
Section: @Erspublicationsmentioning
confidence: 70%
“…The authors conclude that activin-A is not an innocent bystander but plays an active role in cigarette smoke induced pulmonary inflammation [9].…”
Section: @Erspublicationsmentioning
confidence: 96%
See 1 more Smart Citation
“…Both TGF-β and activin-A signalling pathways have been shown to be activated upon allergen provocation in asthma [21,22]. Emerging evidence underscores the potential impact of activin-A on the regulation of airway inflammation and remodelling [22][23][24][25][26][27]. Previous studies by our group and others have demonstrated an anti-inflammatory role for activin-A in various settings [28][29][30][31], while other studies have shown opposing effects [23,24].…”
Section: Introductionmentioning
confidence: 96%
“…Emerging evidence underscores the potential impact of activin-A on the regulation of airway inflammation and remodelling [22][23][24][25][26][27]. Previous studies by our group and others have demonstrated an anti-inflammatory role for activin-A in various settings [28][29][30][31], while other studies have shown opposing effects [23,24]. Interestingly, although the effects of activin-A on airway vascularisation have never been addressed, investigation of its angiogenic effects on other tissues has also produced conflicting results [32][33][34].…”
Section: Introductionmentioning
confidence: 99%